Labour-saving equipment - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
Munachoongo Mulaya, a field officer with the NGO Africare explains how labour-saving farm equipment can be a major advantage for communities who have lost much of their manpower to diseases such as HIV/AIDS